Mallet Finger - Tiffani Dinda Ashar; Helmi Ismunandar (MAJORITY, 2020)
Mallet finger is finger deformity caused by disruption of the extensor tendon terminates at the distal phalanx. The disruption may occur in tendons (tendinous form/ soft tissue form) and bones (bony form / avulsion fracture). These injuries are ubiquitous in workplace and sports. Anamnesis need include patient’s recent history likely mechanism of injury, present with or without pain, and difficulty using affecting finger. The examination found passively reducible mallet deformity, swelling, and or ecchymosis of dorsal distal interphalangeal joint (DIPJ), and pressure in painful. The lateral and anteroposterior x-ray will usually confirm the diagnosis. Most mallet injuries can be treated nonsurgical by splinting, surgery is occasionally recommended. Overall goals of treatment are to restore active DIPJ extension, maintain DIPJ flexion, prevent the development of secondary deformity, avoid subluxation of the DIP joint, and minimize the risk of post-traumatic arthritis.